The Use of ChatGPT as a Learning Tool Among Jordanian Students in Technical Universities: Attitudes and Perceptions - Altikriti, Sahar; Nemrawi, Ziad (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The rapid advancement of technology, particularly with the emergence of artificial intelligence (AI) language models such as Chat Generative Pre-Trained Transformer (ChatGPT), has significantly transformed various domains, especially in education. While ChatGPT has revolutionized complex task performance by enabling personalized learning and automated assessments, its application raises significant concerns about academic integrity. This study investigates the attitudes and perspectives of undergraduate students at Al Hussein Technical University (HTU) toward using ChatGPT in educational settings and the challenges they encounter. Data were collected through a questionnaire administered to 110 undergraduate students, comprising 15 items rated on a three-point Likert scale. The study’s findings indicate that 66% of students are aware of the use of ChatGPT, with 56% expressing comfort in its use, indicating a substantial integration of this technology within educational settings. However, concerns about its reliability persist, with only 43% affirming its accuracy and 26% expressing disagreement. Nonetheless, 67.5% recognize its efficiency, time-saving benefits, and potential to enhance learning. While ChatGPT is useful for brainstorming and idea generation, 79% of students reported hesitance to use it for at-home assessments, indicating persistent apprehensions related to academic integrity. The findings suggest that integrating ChatGPT in educational settings requires addressing reliability and ethical issues through targeted training and clear guidelines. This study advocates incorporating ChatGPT into the HTU curriculum as a complementary resource, balanced with human intellectual engagement, to optimize academic performance and student learning.